PENGARUH TEKNIK MODELLING TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS VII SMP NEGERI 2 KAUMAN - sari, Citra Ayu Kumala; Yuniar, Mila (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
The purpose of this study is to examine the effect of the use of modelling techniques for student learning independence of 7th grade of Junior High School 2 Kauman. In this research, the researcher will uses quantitative approach with the experiment type and use Non-Equivalent Control Groub Design. Subject in this research, the researcher use 7th grade of Junior High School. Data Collecting Method uses interview, observation, and measuring scale, while the research instrument used by researcher is learning independence scale and modelling technique book. Than for data analiysis uses t-test like independent sample t-test and paired sample t-test, that before that there is base assumption test use normality test and homogenity test. The results of this study indicate that there are different average from student pre-test and post-test from experiment class. And that know from paired sample t-test score from 2-tailed value 0,001< 0,05. Than data from independent sample t-test with thw sig 2-tailed value 0,000 < 0,05 so that spoken if there are different signifficantly before and after giving treatment with modelling technique to student learning independence for 7th grade of Junior High School 2 Kauman.